Herramienta de análisis en el plano para estructuras reticuladas - Franco Bohorquez, Ronald Bolivar (Machala: Universidad Tëcnica de Machala, 2019)
In the present technological proposal, the development of an analysis tool using Matlab computer software is proposed, which makes it possible to systematize the method of stiffness applied to reticulated flat structures in order to obtain the internal forces in the bars and the displacements in the knots. Following the methodology of Extreme Programming, developed to guide the process of developing applications or software in a short period of time. Mainly, the needs of the clients were taken into account; visualize the matrices of global stiffness of the structure, and see the calculations made in the background to obtain the stresses and deformations in the structure that is entered. To comply with the users' requirements, a timeline with deadlines for each iteration is established, which serve to create and improve the graphic interface, functionality, or user - machine interaction, in order to make the graphic interface more efficient . At the end of the iterations the result is a complete graphical interface with all the necessary fields to analyze the reticular structure using the stiffness method. Once the definitive graphical interface for the proposed analysis tool has been defined, the procedure to be followed is explained in order to interactively model the reticulated structure formed by; knots, bars, supports, and joints; Also define and assign geometric properties to the elements type bars; area and inertia, modulus of elasticity and likewise enter point and distributed loads. The analysis tool allows to model lattice-like gantry structures, reinforcements and beams, with embedded or articulated elements, with or without displacements imposed on the supports, with point loads at the nodes and distributed trapezoidal loads on the bars, with or without displacements imposed in the supports and that are also on a plane parallel to the horizontal axis or inclined to it. Once the reticulated structure is modeled in the analysis tool, it is possible to choose the processes that the user wants to visualize, among these are included; local bar stiffness matrixes, transformation matrixes, global bar stiffness matrixes, global structure stiffness matrix, global knot load vectors, global bus load vectors, global displacement vectors, internal stresses of the bars and deformations in knots. These results are shown in the Matlab console that can later be exported to PDF format with the possibility of exporting the vectors and matrices obtained to a spreadsheet. After the tool executes the analysis to the structure, it allows to visualize the graphs of moment, shear, axial and displacements on the structure, in addition to the moment and shear equations that allow to obtain these efforts at a distance x from the start node of each modeled bar. Finally, to validate the results obtained by the analysis tool, it is compared with the results obtained by a commercial software that serves as a reference to obtain the percentage of error between both analyzes, giving confidence to the users that the results obtained by the proposed tool in this titling project they are practical and precise.
En la presente propuesta tecnológica se plantea el desarrollo de una herramienta de análisis utilizando el software informático Matlab que permita sistematizar el método de la rigidez aplicada a estructuras planas reticuladas con la finalidad de obtener los esfuerzos internos en las barras y los desplazamientos en los nudos. Siguiendo la metodología de Extreme Programming, desarrollada para guiar el proceso de desarrollo de aplicaciones o software en un corto periodo de tiempo. Principalmente se tuvo en cuenta las necesidades de los clientes; visualizar las matrices de rigidez global de la estructura, y ver los cálculos efectuados en segundo plano para obtener los esfuerzos y deformaciones en la estructura que se ingrese. Para cumplir con las exigencias de los usuarios se establece un cronograma con fechas límites para cada iteración, las cuales sirven para crear y mejorar la interfaz gráfica, la funcionalidad, o la interacción usuario – máquina, con la finalidad de hacer más eficiente la interfaz gráfica. Al culminar las iteraciones el resultado es una interfaz gráfica completa con todos los campos necesarios para analizar la estructura reticular empleando el método de rigidez. Una vez definida la interfaz gráfica definitiva para la herramienta de análisis propuesta, se explica el procedimiento a seguir para modelar de forma interactiva la estructura reticulada conformada por; nudos, barras, apoyos, y articulaciones; Además definir y asignar propiedades geométricas a los elementos tipo barras; área e inercia, módulo de elasticidad y de igual forma ingresar las cargas puntuales y distribuidas. La herramienta de análisis permite modelar estructuras planas reticuladas tipo pórtico, armaduras y vigas, con elementos empotrados o articulados, con o sin desplazamientos impuestos en los apoyos, con cargas puntuales en los nudos y cargas distribuidas trapezoidales sobre las barras, con o sin desplazamientos impuestos en los apoyos y que además están sobre un plano paralelo al eje horizontal o inclinados a este. Una vez modelada la estructura reticulada en la herramienta de análisis, es posible escoger los procesos que desee visualizar el usuario, entre estos se incluyen; matrices de rigideces locales de las barras, matrices de transformación, matrices de rigideces globales de las barras, matriz de rigidez global de la estructura, vectores de cargas en nudos global, vectores de cargas en las barras global, vectores de desplazamientos global, esfuerzos internos de las barras y deformaciones en nudos. Estos resultados se muestran en la consola de Matlab que posteriormente puede ser exportada a formato PDF con la posibilidad de exportar los vectores y matrices obtenidas a una hoja de cálculo. Luego de que la herramienta ejecuta el análisis a la estructura, esta permite visualizar las gráficas de momento, cortante, axial y desplazamientos sobre la estructura, además de las ecuaciones de momento y cortante que permiten obtener estos esfuerzos a una distancia x del nudo de inicio de cada barra modelada. Finalmente, para validar los resultados obtenidos por la herramienta de análisis se compara con los resultados obtenidos por un software comercial que sirve de referente para obtener el porcentaje de error entre ambos análisis, dando confianza a los usuarios de que los resultados obtenidos por la herramienta propuesta en este proyecto de titulación son prácticos y precisos.
Keywords: RIGIDEZ; ESTRUCTURA; ANÁLISIS MATRICIAL; ESFUERZO